Motion Capture Technology and Its Applications in Film and Television Animation - Yong Guo; Chan Zhong (Advances in Multimedia)
In order to improve the production effect of film and television animation, this paper combines motion capture technology to construct a film and television animation production system and proposes a simple correction method to eliminate the instability of animation frames. This method suppresses the occurrence of instability by introducing additional viscosity corresponding to shear waves in the vicinity of strong shock waves. Furthermore, this paper constructs two Riemannian solvers, HLLEC and HLLES, to study the stability of numerical carbuncle problems. In addition, this paper builds a film and television animation production system based on motion capture technology. Through the verification of motion capture and animation production effects, it can be seen that the film and television animation system based on motion capture technology proposed in this paper can effectively promote the improvement of the animation production effect.